2021
DOI: 10.3390/nu13113917
|View full text |Cite
|
Sign up to set email alerts
|

Who We Seek and What We Eat? Sources of Food Choice Inspirations and Their Associations with Adult Dietary Patterns before and during the COVID-19 Lockdown in New Zealand

Abstract: Research shows the shaping of food choices often occurs at home, with the family widely recognised as significant in food decisions. However, in this digital age, our eating habits and decision-making processes are also determined by smartphone apps, celebrity chefs, and social media. The ‘COVID Kai Survey’ online questionnaire assessed cooking and shopping behaviours among New Zealanders during the 2020 COVID-19 ‘lockdown’ using a cross-sectional study design. This paper examines how sources of food choice in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…While it is not possible to quantify these changes using the FFQ, a consideration of how the pandemic has altered dietary behaviors over the long term deserves further investigation. A recent publication on dietary intakes during the COVID-19 pandemic response in NZ demonstrated an “overall shift toward an unhealthy eating pattern” with an increased consumption of sweet snacks (41%), salty snacks (33%), and sugary drinks (20%) during the lockdown, with those aged under 50 years more likely to report adverse changes to dietary habits [ 26 ] and a notable increase in the use of ‘comforting’ recipes during the lockdown, which was associated with higher scoring in the ‘Unhealthy DP’ [ 27 ]. Both studies reported an overall decrease in the nutritional quality of diets during the COVID-19 pandemic [ 26 , 27 ], which may explain, to some degree, the relatively low adherence to the NZ Dietary Guidelines found in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is not possible to quantify these changes using the FFQ, a consideration of how the pandemic has altered dietary behaviors over the long term deserves further investigation. A recent publication on dietary intakes during the COVID-19 pandemic response in NZ demonstrated an “overall shift toward an unhealthy eating pattern” with an increased consumption of sweet snacks (41%), salty snacks (33%), and sugary drinks (20%) during the lockdown, with those aged under 50 years more likely to report adverse changes to dietary habits [ 26 ] and a notable increase in the use of ‘comforting’ recipes during the lockdown, which was associated with higher scoring in the ‘Unhealthy DP’ [ 27 ]. Both studies reported an overall decrease in the nutritional quality of diets during the COVID-19 pandemic [ 26 , 27 ], which may explain, to some degree, the relatively low adherence to the NZ Dietary Guidelines found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The study had a large sample size and used appropriate sampling methods, but the results cannot be generalized, as our population was predominantly female (88%), was of NZ European ethnicity (74%), and had completed some form of higher education; therefore, it is not fully representative of the NZ population, and caution is recommended when interpreting these findings. This research was also conducted during the COVID19 pandemic, which has been documented to have affected the nutritional quality of dietary intakes [ 26 , 27 ]. Dietary intake was measured using a population-validated FFQ but was based on self-reported data and is subject to recall bias.…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems that this aspect can also be very interesting. For example, Roy et al observed that the score reflecting healthy diet patterns was significantly higher among the respondents influenced by nutrition experts and family and friends than others [ 72 ]. Interestingly, scores calculated for the so-called meat dietary pattern were significantly higher among those inspired by celebrity cooks but also by family.…”
Section: Discussionmentioning
confidence: 99%
“…Eating habits also changed for some people towards healthier and for others towards unhealthier practices than before the pandemic ( Gerritsen et al, 2021 ; Laguna, Fiszman, Puerta, Chaya, & Tárrega, 2020 ). For example, during lockdowns in New Zealand, increased consumption of sweet snacks (41%), salty snacks (33%), alcohol (33%), and sugary drinks (20%) ( Gerritsen et al, 2021 ) and use of ‘comforting’ recipes (75.8%) ( Roy et al, 2021 ) were reported. A French study found mixed results with some people eating fresher products (i.e., fruits and vegetables) and others eating more comfort food or snacking ( Sarda et al, 2022 ).…”
Section: Disruption In Food Practices During Covid-19mentioning
confidence: 99%